Driving and Inhibiting Factors of Stunting Child Care Behavior in Padang Lawas District - Nur Amri Sari Harahap; Kintoko Rochadi; Zulhaida Lubis (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
One of the nutritional problems experienced by children in Indonesia is stunting. Stunting itself is a condition of poor child growth and development. The researcher aims to explore the driving factors and inhibitors of stunting parenting behavior in Padang Lawas Regency. The type of research used in the study was qualitative research with a descriptive phenomenological approach. This research was conducted at three health centers: Sibuhuan Health Center, Tanjung Botung Health Center, and Ujung Batu Health Center in July 2022-January 2023. In this study, the number of participants was ten people consisting of mothers, community leaders, and regional heads. The data analysis in this study was carried out by content analysis immediately after each interview process, namely at the same time as the data transcript was made. The results of interviews about mothers' knowledge in fulfilling children's nutrition found that the majority of mothers have good knowledge in fulfilling nutrition in general, where mothers know about the definition of exclusive breast milk and its benefits, know the right time to give complementary foods for breast milk and the types of foods that must be present in the child's plate in fulfilling their nutrition. This study concludes that positive parenting behavior occurs when there is a driving force for positive behavior; the driving factors found in this study are knowledge, access to information, and support from health workers. At the same time, the mother's parenting behavior is negative if there are restraining forces that prevent her from positive behavior. It is recommended to the Ujung Batu, Tanjung Botung and Sibuhuan Community Health Centers to provide health education on exclusive breastfeeding and appropriate complementary foods for toddlers and to collaborate with cross-sectors in preventing stunting through changing behavior in fulfilling child nutrition. Keyword: Breast Milk, Behavior, Complementary Foods, Parenting, Stunting